Van der Waals epitaxial two-dimensional CdSxSe(1−x) semiconductor alloys with tunable-composition and application to flexible optoelectronics. Issue 36 (11th September 2017) - Xia, Jing; Zhao, Yun-Xuan; Wang, Lei; Li, Xuan-Ze; Gu, Yi-Yi; Cheng, Hua-Qiu; Meng, Xiang-Min
Abstract : 2D non-layered CdS x Se(1− x ) alloys with a tunable composition have been synthesized by incommensurate VDWs epitaxy and possess huge application potential in next-generation optoelectronics. Abstract : Despite the substantial progress in the development of two-dimensional (2D) materials from conventional layered crystals, it still remains particularly challenging to produce high-quality 2D non-layered semiconductor alloys which may bring in some unique properties and new functions. In this work, the synthesis of well-oriented 2D non-layered CdS x Se(1− x ) semiconductor alloy flakes with tunable compositions and optical properties is established. Structural analysis reveals that the 2D non-layered alloys follow an incommensurate van der Waals epitaxial growth pattern. Photoluminescence measurements show that the 2D alloys have composition-dependent direct bandgaps with the emission peak varying from 1.8 eV to 2.3 eV, coinciding well with the density functional theory calculations. Furthermore, photodetectors based on the CdS x Se(1− x ) flakes exhibit a high photoresponsivity of 703 A W −1 with an external quantum efficiency of 1.94 × 10 3 and a response time of 39 ms. Flexible devices fabricated on a thin mica substrate display good mechanical stability upon repeated bending. This work suggests a facile and general method to produce high-quality 2D non-layered semiconductor alloys for next-generation optoelectronic devices.